2020
DOI: 10.31234/osf.io/h3uwq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performing a task jointly enhances the sound-induced flash illusion

Abstract: Our different senses are stimulated continuously. Through multisensory integration, different sensory inputs may or may not be combined into a unitary percept. Simultaneous with this stimulation, people are frequently engaged in social interactions, but how multisensory integration and social processing combine is largely unknown. The present study investigated if, and how, the multisensory sound-induced flash illusion is affected by a social manipulation. In the sound-induced flash illusion, a participant typ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As shown in Figure 4 the SOA between the first and the second tone systematically alters the strength of the illusion, therefore selection of these parameters has important consequences for performance. It has recently been shown that performing the SIFI task with a confederate present can enhance the illusion (Wahn et al, 2020). This study asked the confederate to judge the number of beeps, whilst the participant judged the number of flashes.…”
Section: The Sifi Paradigm: Stimulus Parameters and Guidance For Future Researchmentioning
confidence: 99%
“…As shown in Figure 4 the SOA between the first and the second tone systematically alters the strength of the illusion, therefore selection of these parameters has important consequences for performance. It has recently been shown that performing the SIFI task with a confederate present can enhance the illusion (Wahn et al, 2020). This study asked the confederate to judge the number of beeps, whilst the participant judged the number of flashes.…”
Section: The Sifi Paradigm: Stimulus Parameters and Guidance For Future Researchmentioning
confidence: 99%
“…It was shown that groups achieve collective benefits in joint visuomotor tasks that require coordination between eyes and hands (Ganesh et al, 2014;Knoblich and Jordan, 2003;Newman-Norlund et al, 2008;Reed et al, 2006;Takagi et al, 2017). Other research (Brennan and Enns, 2015b;Neider et al, 2010;Wahn et al, 2017a;Wahn and König, 2016) has shown that there are benefits to working together on tasks that involve finding or following objects in different places. Also, Rajaram and Pereira-Pasarin (2010) and Bietti and Sutton (2015) showed that there are benefits for the group when people work together to remember things.…”
Section: Collective Benefitsmentioning
confidence: 99%